2012
DOI: 10.1016/j.pain.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory pain is associated with increased excitability and hyperpolarization-activated current ( I h) in C- but not Aδ-nociceptors

Abstract: Inflammatory pain hypersensitivity results partly from hyperexcitability of nociceptive (damage-sensing) dorsal root ganglion (DRG) neurons innervating inflamed tissue. However, most of the evidence for this is derived from experiments using acute inflammatory states. Herein, we used several approaches to examine the impact of chronic or persistent inflammation on the excitability of nociceptive DRG neurons and on their expression of I(h) and the underlying hyperpolarization-activated cyclic nucleotide-gated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
131
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 74 publications
18
131
3
Order By: Relevance
“…The frequency of spontaneous activity in naïve rats ranges from ϳ0.3 Hz to 1.0 Hz. (32,36). Colon inflammation increased this frequency to ϳ2 Hz in our study, while modified spinal nerve axotomy/nerve ligation increased it to about 4 Hz.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The frequency of spontaneous activity in naïve rats ranges from ϳ0.3 Hz to 1.0 Hz. (32,36). Colon inflammation increased this frequency to ϳ2 Hz in our study, while modified spinal nerve axotomy/nerve ligation increased it to about 4 Hz.…”
Section: Discussioncontrasting
confidence: 38%
“…By contrast, the discharge frequency of evoked action potentials is several-fold greater (10 to 30 Hz in colon afferents and 10 to 120 Hz in dorsal horn neurons at various distension pressures). It is likely that other parameters of spontaneous activity, such as the recruitment of different types of afferent fibers, (C and A␦, A␤ fibers) (8,17,32,35) and their differential projection sites in the brain structures also play a role in inducing specific neuropathies in clinical diseases, such as autoimmune diseases, metabolic disease, cardiovascular disease, and cancer. Each disease or type of injury (4) induces a unique profile of inflammatory mediators (cytokines, chemokines, free radicals, iNOS, and metabolites of arachidonic acid) and, therefore, the nerve lesion and the resulting modifications of afferent neurons to induce different neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been other studies that have examined the functional role of HCN channels in neuropathic pain, these previous studies have mainly utilized animal models that involve axonotmesis, e.g. SNL and CCI (Chaplan et al, 2003;Lee et al, 2005;Sun et al, 2005;Luo et al, 2007;Jiang et al, 2008;Emery et al, 2011) or chronic hind limb inflammation (Weng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although ZD7288 was not applied directly to the nerve in behavioral experiments, previous studies have shown that <10 mg/kg doses of ZD7288 administered by intravenous infusion rapidly suppress A-fiber ongoing activity within 10 min in the SNL model (Lee et al, 2005) and C-fiber ongoing activity in a model of chronic hind limb inflammation (Weng et al, 2012). Based on the current data, as well as these previous studies, we have therefore proposed that the reversal of heat hypersensitivity by ZD7288 may be due to a partial reduction in C-fiber ongoing activity.…”
Section: Role Of Hcn Channels In the Maintenance Of Neuritisinduced Omentioning
confidence: 99%
See 1 more Smart Citation